1991
DOI: 10.1037/0097-7403.17.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Transitive inference formation in pigeons.

Abstract: Pigeons were trained with 4 pairs of visual stimuli in a 5-term series-A+ B-, B+ C-, C+ D-. and D+ E-(in which plus[+] denotes reward and minus(-] denotes nonreward)-before the unreinforced test pair B D was presented. All pigeons chose Item 8, demonstrating inferential choice. A novel theory (value transfer theory), based on reinforcement mechanisms, is proposed. In Experiment 2, the series was extended to 7 terms. Performance on test pairs was transitive, and performance on training pairs accorded with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
368
2
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(391 citation statements)
references
References 12 publications
20
368
2
1
Order By: Relevance
“…Previous studies have demonstrated that several animal species can learn an overlapping series of discrimination problems and demonstrate a capacity for transitive inference (15,(26)(27)(28)(29)(30)(31)(32). The present results identify the hippocampal region as critical to transitive inference and indicate that the hippocampus plays a critical role in the development or flexible expres- sion of a representation of orderly relations among stimulus items.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have demonstrated that several animal species can learn an overlapping series of discrimination problems and demonstrate a capacity for transitive inference (15,(26)(27)(28)(29)(30)(31)(32). The present results identify the hippocampal region as critical to transitive inference and indicate that the hippocampus plays a critical role in the development or flexible expres- sion of a representation of orderly relations among stimulus items.…”
Section: Discussionsupporting
confidence: 50%
“…An additional phenomenon, typically observed for comparisons involving a closed-set series for which only ordinal information is available (e.g., an arbitrary ordering of elements for which magnitude information is not provided), is a bow-shaped serial position curve: accuracy and decision time indicate greater difficulty for pairs drawn from near the center of the list than for pairs closer to the ends. A bowed serial position curve is not observed for magnitude continua such as those on which we have focused in the present paper, but it is found for arbitrary orderings, both for humans (e.g., Potts, 1974;Trabasso & Riley, 1975;Woocher et al, 1978) and many animal species, including squirrel monkeys (McGonigle & Chalmers, 1977), rats (Davis (1992) and pigeons (von Fersen et al, 1991; for a review see Merritt & Terrace, 2011).…”
Section: Limitations and Possible Extensions Of The Bartlet Modelmentioning
confidence: 47%
“…For example, under certain conditions the Rescorla-Wagner model of associative learning (Rescorla & Wagner, 1972;see Wynne, 1995) can model qualitative aspects of animals' ability to infer transitivity of choice (e.g., after being trained on only adjacent pairs of stimuli exhibiting the reward pattern A > B, B > C, C > D, D > E, an animal will tend to choose B over D). Other associative models can account for learning of orderings across a broader range of conditions (von Fersen, Wynne, Delius, & Staddon, 1991).…”
Section: Multiple Levels Of Representation For Comparative Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative associative models of transitive inference in both primates and nonprimates have received increased attention in recent years (e.g., Delius & Siemann, 1998;Wynne, 1997). Some such models are based either on direct reinforcement histories of test stimuli (e.g., Couvillon & Bitterman, 1992) or associative value transfer in which the rewarded member of a stimulus pair transfers some of its associative strength or value to the nonrewarded pair item (von Fersen, Wynne, Delius, & Staddon, 1991). Studies of social concepts, which are addressed elsewhere in this issue by Seyfarth & Cheney, provide additional evidence of associative processes being the representation "glue" in monkeys rather than the more abstract propositional encoding of the human investigators (cf., Thompson, 1995;Seyfarth & Cheney, 1997).…”
Section: Resemblance By Relation or By Association?mentioning
confidence: 99%